Le sanctuaire gallo-romain de Drevant (Cher) : état des connaissances et nouvelle approche archéologique des façades sud et est - Frédéric Méténier (Revue Archéologique du Centre de la France)
Archaeological excavations conducted in 2007 and 2008 on Drevant Gallo-Roman Sanctuary (Cher) intervened through a project of restoration and development of ancient masonry commanded by Historic Monuments Regional Conservation. These excavations were prescribed and controlled by the archaeological service of Region Centre. Occupation of the site begins from the second Iron Age but the first perennial installations are performed in the augustan period with the creation of a simple peribolos careful construction. This construction is quickly with a second wall recessed from the Eastern façade leading to the creation of a covered gallery (porticus). At the centre of the eastern front, a pavilion whose monumental perron is conserved is also done. The second half of the first century of our era sees the creation of a new monumental access to the Southwest. All is likely destroyed by fire in the last quarter of the first century.A new more homogeneous architectural program was born to the transition between the 1st and the 2nd century, with the implementation of a second peribolos within the original walls to create galleries of peripheral circulation around the temenos. These spaces, galleries, and sacred area are backfilled to implement of new concrete floors, tuileaux and limestone. Two monumental access are levelled, the South-West corner is closed while a new monumental threshold is created on the eastern front. On Northeast and Southeast corners, pavilions installed on caissons-foothills tying the Eastern façade. Finally, at the end of the roman era, the western façade is punctuated by three exedras with flat bedside, two for apse internal. The destination of these constructs is unknown but may reflect a modification of cults or a change of devolution of the site.